The effectiveness of United Nations multifunctional peace-support - comparing conflict transformation in Angola and Mozambique - Kornprobst, Markus (Department of Political Studies, 2023)
This study evaluates the effectiveness of United Nations multifunctional peace-support in facilitating the transformation of the Angolan and the Mozambican internal wars into non-violent conflicts which are managed within the framework of a newly created polity. The comparison between the Angolan case, a failure, and the Mozambican case, a success, aims to contribute towards an answer to the question of under which conditions the concept of United Nations multifunctional peace-support fails and under which conditions it is successful. Since both the conflict situations in Angola and Mozambique and the kinds of United Nations intervention (in both cases multifunctional peace-support operations) were similar in many respects, the research format of this comparison is a most-similar-systems design. Similarities and differences of multifunctional peace-support operations as well as of the Angolan and the Mozambican conflict situations are outlined. The argument of this study is that a few significant differences between the Angolan case and the Mozambican case explain the fundamentally different outcomes of the two conflict transformation processes. The Angolan parties concluded a peace agreement due to a combination of two main causes: strong external pressure and military stalemate. External pressure, however, decreased after the peace agreement was concluded, and, equally important, the implementation of the accord created a new military situation. The United Nations, restricted by a lack of resources and a very limited mandate, was incapable of countering this threat. The party which perceived itself as loser of the conflict transformation process went back to war. The Mozambican parties, by contrast, agreed upon a conflict transformation process due to a combination of three main causes: external pressure, military stalemate and complete economic exhaustion. The beginning of the conflict transformation process along with the United Nations intervention altered the military situation as it had in Angola, but external pressure and the state of complete economic exhaustion persisted. The United Nations, having a comprehensive mandate and sufficient resources, repeatedly proved to be capable of putting the conflict transformation process back on track when it was stalled. Most importantly, it was highly effective in facilitating political solutions to problems arising from the implementation of the peace accord by offering financial resources to the exhausted conflict parties. The failure of multifunctional peace-support in Angola and the success of the concept in Mozambique suggest four conditions necessary for the success of this kind of United Nations intervention: first, external pressure must not stop once negotiations for a peace agreement have been successfully concluded but must persist throughout the entire conflict transformation process. Second, the conflict parties must perceive conflict transformation as gain. Third, multifunctional peace-support operations need a comprehensive mandate. Fourth, multifunctional peace-support operations need sufficient resources.